2022
DOI: 10.1017/s1047951122003092
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and respiratory muscle strength in children and adolescents with CHD: systematic review and meta-analysis

Abstract: Patients with CHD are less active if compared with controls and have limited functional capacity, related to muscle weakness and fatigue. The aim of this study was to evaluate the peripheral and respiratory muscle strength of children and adolescents with CHD with systematic review and meta-analysis. The review included observational and randomised control trial studies which evaluated peripheral and respiratory muscle strength in children and adolescents with CHD under 18 years old. The peripheral muscle stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The data of a systematic review and meta-analysis published in October 2022, confirmed that children and adolescents (under 18 years of age) with CHD have reduced muscle strength compared to the control group (-34 .07 N•m), and although the meta-analysis did not reveal any significant difference in hand muscle strength between these two groups (0 .08 N•m), it showed a decrease in muscle strength of limbs in the group of children with CHDs . The authors also noted that patients with CHDs are characterized by lower strength of respiratory muscles [16] .…”
Section: Muscle Strengthmentioning
confidence: 97%
“…The data of a systematic review and meta-analysis published in October 2022, confirmed that children and adolescents (under 18 years of age) with CHD have reduced muscle strength compared to the control group (-34 .07 N•m), and although the meta-analysis did not reveal any significant difference in hand muscle strength between these two groups (0 .08 N•m), it showed a decrease in muscle strength of limbs in the group of children with CHDs . The authors also noted that patients with CHDs are characterized by lower strength of respiratory muscles [16] .…”
Section: Muscle Strengthmentioning
confidence: 97%
“…Most young people with CHD are less physically active than their healthy peers, 14 putting them at risk of becoming sedentary adults and acquiring latent chronic diseases. 15 Barriers to physical activity in youth with CHD are multifactorial: reduced aerobic capacity inherent to the cardiac disease, 2 impaired muscle function, 16 impaired lung function, 17 low self-concept and self-efficacy, 18 parental attitude, 19 home and health environment, 20 or restriction recommendations by physicians. 21 Ultimately, adults with CHD have a higher burden of adverse cardiovascular events relative to the general population and a high prevalence of smoking, obesity, hypertension, hyperlipidaemia, and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%